Relationship marketing : a consumer experience approach - Baron, Steve; Conway, A. (Anthony); Warnaby, Gary (Los Angeles, CA : Sage, 2010)
The relationship between a market and a consumer is complex. Far from simply being an exchange of services, there is an often complex transaction of feeling, meaning and experience. This book explores the factors of relationship marketing in its contemporary context.
Includes bibliographical references and index.
BSBA
Keywords: Relationship marketing; Customer relations